Economic Growth and Development in Ethiopia (Perspectives on Development in the Middle East and North Africa (MENA) Region, 2018)
This volume is a collection of selected empirical studies on determinants of economic growth and development in Ethiopia.The core argument for editing this book is to provide an up-to-date picture of the state and patterns of growth and development in Ethiopia. Ethiopia has been under focus in the past due to draughts, war, famine, development changes and the effects of global economic crisis in the country. A main contribution of this volume is that it helps identify selected important determinants of growth and development in Ethiopia and provides an estimation of their effects using up-to-date data, modelling and methods. Taken together the studies provide a comprehensive picture of the state of growth and development, their measurements, causal relationships and evaluation of efficient policies and practices in achieving progress in Ethiopia. The issues covered represent major challenges to the government and development organizations who are aiming at achieving higher growth and alleviating poverty in the country. The studies cover transition from rural agriculture to urban industry and the development of services.